DBOX Arena Padangpanjang in Corporate Photography: Visual Branding Strategy through Commercial Photography - Suci Oktalif Rahmadani; Ivan Saputra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
DBOX Arena Padangpanjang is the first modern culinary and sports tourism destination in Padangpanjang City, West Sumatra, integrating a mini soccer field, futsal court, a cafe (Nagura Coffee), and a children's playground amid a natural rice-field landscape. Having operated only since December 2023, DBOX Arena has not yet possessed an optimal photography-based visual identity for its branding and promotion. This creative work aims to produce a series of commercial photographs through a corporate photography approach to build a professional image and communicate DBOX Arena's facilities comprehensively to the public. The creation method consisted of a preparation stage (site observation, interviews, and visual concept sketching), an execution stage (field photo shoots), and a post-production stage (editing, selection, cropping, and colour grading). Shooting was carried out both indoors and outdoors using a mix-lighting technique and aerial photography with a drone to capture the site's geographical beauty. Supporting theories applied include photographic composition theory, corporate photography theory, and digital-imaging theory. The project produced 52 selected photographic works (single and series photographs). By using one consistent family model, the photographs convey a narrative of warmth, togetherness, happiness, and safety in family recreational activities at DBOX Arena. Through the architectural visualisation of the building, the culinary offerings, staff interaction, and the site's aesthetic panorama, this corporate photography work is expected to strengthen the company's brand identity, enrich the academic literature on commercial photography, and serve as an effective marketing medium in digital and print form.